2017
DOI: 10.1111/avj.12649
|View full text |Cite
|
Sign up to set email alerts
|

Beak and feather disease virus carriage by Knemidocoptes pilae in a sulphur‐crested cockatoo (Cacatua galerita)

Abstract: This case highlights the potential immunosuppressive effects of BFDV infection and its potential as a keystone pathogen in the Australian environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Eastwood et al (2019) found the same when analysing BFDV infection in P. elegans parents and their offspring in the nest, and consequently they suggested that infection of nestlings with BFDV-negative parents may have occurred through contaminated nesting material. Alternatively, the BFDV-positive birds in our study may have been infected through ectoparasitic vectors instead of through the nesting material itself, as BFDV has been found in mites on cockatoos (Portas et al, 2017). Exposure to high doses of BFDV is thought to be required to establish infection (Raidal & Peters, 2018).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Eastwood et al (2019) found the same when analysing BFDV infection in P. elegans parents and their offspring in the nest, and consequently they suggested that infection of nestlings with BFDV-negative parents may have occurred through contaminated nesting material. Alternatively, the BFDV-positive birds in our study may have been infected through ectoparasitic vectors instead of through the nesting material itself, as BFDV has been found in mites on cockatoos (Portas et al, 2017). Exposure to high doses of BFDV is thought to be required to establish infection (Raidal & Peters, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…BFDV is thought to be transmitted directly between individuals through faeces, contaminated feather dust and crop secretions (Ritchie et al, 1991), as well as from mothers to embryonated eggs (Rahaus et al, 2008). It was found in mites infesting a BFDV-positive cockatoo, suggesting that it may be transmitted through ectoparasitic vectors (Portas et al, 2017). BFDV is considered highly stable in the environment (Raidal & Peters, 2018;Todd, 2000) because it is resistant to heat, surviving exposure to high temperatures, for example, 80 • C for 30 min (Raidal & Cross, 1994), and many disinfectants (Jackson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, it occurs in raptors and other birds following predation and/or opportunistic feeding upon the tissues or excretions of BFDV-affected parrots and cockatoos. Knemidokoptes mites have recently been shown to concentrate BFDV within their faeces [11] which raises the possibility of ectoparasites such as hippoboscid flies acting as fomites and vectors of transmission particularly to insectivorous bird species such as the rainbow bee-eater. Interestingly, while interseasonal nest hollow sharing may promote the circulation of novel BFDV genotypes in psittacine populations, species such as raptors, which retain nest hollows over many seasons, may not have sufficient intraspecific transmission frequencies to permit permanent host switching.…”
Section: Structure Of Beak and Feather Disease Virusmentioning
confidence: 99%
“…Identification of beak and feather disease virus (BFDV) in the gut of mites in a wild sulphur‐crested cockatoo confirms a novel transmission vector for this virus. The study raises implications for biosecurity and quarantine measures to prevent the spread of the virus into captive flocks of psittacine birds …”
Section: Avianmentioning
confidence: 99%
“…The study raises implications for biosecurity and quarantine measures to prevent the spread of the virus into captive flocks of psittacine birds. 8 The cockatoo was presented with advanced skin and feather lesions consistent with BFDV. Pathological investigation showed the presence of Knemidocoptes mites, as well as BFDV antigen in keratinocytes and in the gut of the mites.…”
Section: Avianmentioning
confidence: 99%